2012
DOI: 10.7306/gq.1079
|View full text |Cite
|
Sign up to set email alerts
|

New magnetic anomalies of the Outer Capathians in NE Slovakia and their relationship to the Carpathian Conductivity Zone

Abstract: Hith erto un known mag netic anom a lies have been de tected while as sem bling a mag netic pic ture of the Slovakian ter ri tory. An im pres sive mag netic anom aly was rec og nized in the northeasternmost part of Slovakia as so ci ated with sed i men tary rocks of the flysch belt. This is a rare phe nom e non, be cause the flysch se quence in Slovakia typ i cally lacks mag netic rocks. Thus, an ig ne ous body in truded into the flysch might cause the anom aly. The shape and the char ac ter of the anom a lous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The Zboj-1 bore hole lies close to this anom aly. The flu ids there dis play a var ied com po si tion and a tem per a ture range of 130-220°C for in clu sions in quartz (Kuchariè et al, 2013). That in ter val is con cor dant with the tem per a tures obtained from re-cal cu la tion of vitrinite reflectance val ues (128-178°C).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The Zboj-1 bore hole lies close to this anom aly. The flu ids there dis play a var ied com po si tion and a tem per a ture range of 130-220°C for in clu sions in quartz (Kuchariè et al, 2013). That in ter val is con cor dant with the tem per a tures obtained from re-cal cu la tion of vitrinite reflectance val ues (128-178°C).…”
Section: Discussionmentioning
confidence: 74%
“…Flu ids which con tained mer cury, ar senic, an ti mony, copper and so on mi grated into the Pol ish flysch Carpathians (e.g., in the Krynica, Mêciny and Baligród ar eas), ex plain ing the presence of these el e ments in the BS area. Kuchariè et al (2013) showed that a mag netic anom aly is pres ent in NE Slovakia in the West ern Carpathians. It lies south of Dukla in Po land where the Racza, Dukla and Silesian units out crop (WoŸnicki and Šucha in: Poprawa andNemèok, 1988-1989).…”
Section: Discussionmentioning
confidence: 99%
“…Bezák et al, 1997, segment of Pieninic crust, e.g. Grad et al, 2006 and especially by a much larger influence of the volcanic activity (intrusions into the flysch are also expected, see Kucharič et al, 2012Kucharič et al, , 2013, including the protrusions of partial asthenolites into the flysch strata. Therefore, this area is interesting and promising in terms of geothermal use.…”
Section: Outer Carpathian Flysch Belt In the North-eastern Slovakiamentioning
confidence: 99%
“…Small laccoliths and dykes of high-K calc-alkaline subvolcanic rocks situated near Uherský Brod in southeastern Moravia (Czech Republic), together with occurrences in the Pieniny Mountains (southern Poland) and Nová Sedlica (northeastern Slovakia), represent the only three areas with Neogene magmatism in the Western Outer Carpathians (Nejbert et al 2012;Kucharič et al 2013). From the perspective of evolution of the Carpathian-Pannonian region, the subvolcanic rocks in the vicinity of Uherský Brod have a unique geological position (Harangi et al 2007;Seghedi and Downes 2011) on the border between the Carpathians and the Bohemian Massif (Fig.…”
Section: Introductionmentioning
confidence: 99%